Protocol for a systematic review and meta-analysis on intention to screen for cervical cancer and predictors among women of reproductive age in Ethiopia - Begetayinoral Kussia Lahole; Tesfahun Simon; Wondimu Ewunetu; Wondafrash Kussia (BMJ Public Health)
Introduction The incidence and fatality rates associated with cervical cancer are continuously decreased by cervical cancer screening. However, in underdeveloped nations such as Ethiopia, very few women have undergone cervical cancer screening. There is a scarcity of nationally summarised data in Ethiopia on women’s intention to use cervical cancer screening and its determinants. Therefore, this protocol describes a planned systematic review and meta-analysis that will evaluate the intention to use cervical cancer screening and its predictors among women of childbearing age in Ethiopia.Methods and materials The online databases of EMBASE, PubMed, CINAHL, Web of Science, Cochrane Library, HINARI, Google Scholar, and African Journals online databases will be comprehensively searched from 1 January 2014 to 31 December 2023. The Joanna Briggs Institute quality rating instrument will be used to assess the quality of the included studies. The STATA V.17 statistical software will be used for data analysis. The inverse variance (I2) and Cochran Q statistics will be used to examine the heterogeneity between studies. A random effects model will be used to calculate the pooled prevalence of intention towards cervical cancer screening with a 95% CI. To determine publication bias, a funnel plot, the Egger and Begg test, and a 5% significance level will be used.Ethics and dissemination There is no need for ethical approval. The results will be disseminated to academic beneficiaries and the public.PROSPERO registration number CRD42023440970.